2019
DOI: 10.3390/ijms20030640
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Induced Dysmetabolic Changes Involving Tissue Chromium Mobilization in Female Rats

Abstract: Atypical antipsychotics, such as olanzapine, are commonly prescribed to patients with schizophrenic symptoms and other psychiatric disorders. However, weight gain and metabolic disturbance cause adverse effects, impair patient compliance and limit clinical utility. Thus, a better understanding of treatment-acquired adverse effects and identification of targets for therapeutic intervention are believed to offer more clinical benefits for patients with schizophrenia. Beyond its nutritional effects, studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A previous study has showed that oral gavage (2mg/kg) of olanzapine in rats induced significant weight gain over control beginning at day 5. 30 In addition, chronic olanzapine treatment did not significantly increase liver mass or visceral adiposity in our study. A number of rodent studies have reported that chronic olanzapine treatment does not increase triglyceride and cholesterol plasma levels or induce weight gain independent increases in triglyceride levels.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…A previous study has showed that oral gavage (2mg/kg) of olanzapine in rats induced significant weight gain over control beginning at day 5. 30 In addition, chronic olanzapine treatment did not significantly increase liver mass or visceral adiposity in our study. A number of rodent studies have reported that chronic olanzapine treatment does not increase triglyceride and cholesterol plasma levels or induce weight gain independent increases in triglyceride levels.…”
Section: Discussionmentioning
confidence: 39%
“…In other reports, different delivery routes (oral gavage and intraperitoneal injection) and higher doses (up to 10 mg/kg) were used. 7 , 30 In future studies we will include various doses and harvest the tissue samples at several time points for comparison. Secondly, the use of animal models of psychiatric disorders may also provide more information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study has suggested that Cr can be used as a treatment for psychiatry disease and have a positive impact on the patient’s mood by lowering the functional sensitivity of the serotonin 2A receptor [41]. In Yang’s study, daily intake of Cr supplements can improve the side-effect of anti-schizophrenia drugs such as weight gain and metabolic disorders [42]. Therefore, our results assume that serum Cr concentrations may correlate with antipsychotics; however, whether its concentration is associated with the risk of developing schizophrenia and/or the progress of schizophrenia will require further research.…”
Section: Discussionmentioning
confidence: 99%
“…84 Metabolomics can discover untimely biochemical modifications in disorder and lets in developing predictive biomarkers. 85 In fact, metabolomics appears promising for analysing and identifying metabolic functions that describe certain pathological and physiological states. 86 However, and metabolomics biomarkers need to be helpful for analysis, therapeutics and practical evaluation, the discovery of novel drugs and healing efficacy tracking.…”
Section: Metabolic Biomarkersmentioning
confidence: 99%